2015
DOI: 10.1152/ajpgi.00066.2015
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the pathogenesis of NSAID enteropathy using proton pump inhibitors and a hydrogen sulfide-releasing NSAID

Abstract: The small intestine is a significant site of ulceration and bleeding induced by nonsteroidal anti-inflammatory drugs (NSAIDs). The pathogenesis is poorly understood. The present study explored the roles of bile, bacteria, and enterohepatic circulation to NSAID enteropathy, using both a conventional NSAID (naproxen) and a gastrointestinal-safe naproxen derivative (ATB-346), as well as proton pump inhibitors (PPIs). Rats were treated orally with naproxen or equimolar doses of ATB-346 over a 5-day period, with or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
44
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 62 publications
(100 reference statements)
0
44
0
1
Order By: Relevance
“…38 Mice treated with indole and indomethacin did not have a change in the abundance of Bacteroidia but did have an increase in several members of the gram-positive family Clostridiales in concert with diminution of the severity of intestinal mucosal damage. Evidence exists that the microbiota plays an important role in the development of NSAID enteropathy.…”
Section: Discussionmentioning
confidence: 95%
“…38 Mice treated with indole and indomethacin did not have a change in the abundance of Bacteroidia but did have an increase in several members of the gram-positive family Clostridiales in concert with diminution of the severity of intestinal mucosal damage. Evidence exists that the microbiota plays an important role in the development of NSAID enteropathy.…”
Section: Discussionmentioning
confidence: 95%
“…By contrast, acid inhibition does not confer protection to NSAID-induced damage distal to the ligament of Treitz [16,[22][23][24], and, in fact, studies report that PPIs could contribute to small intestinal injury. Wallace et al [13] and Blacker et al [25] have reported that PPIs exacerbate NSAID-induced small intestinal injury in rodents. Their study showed that PPIs induced a low acid gastric environment that resulted in dysbiosis, which exacerbated NSAID-induced small intestinal injury.…”
Section: Discussionmentioning
confidence: 99%
“…Most of NSAID from the chemical point of view have acid properties with dissociation constant (pKa) 3-5. In the stomach acidic environment, these molecules are easily ionized and penetrate the epithelial cells of gastroduodenal SM, accumulating there and providing a direct damaging effect [14,15]. It was determined, that some time after the administration of these drugs, penetration of hydrogen and sodium ions into SM increasing is observed.…”
Section: Introductionmentioning
confidence: 99%
“…But these drugs safety was proved in patients with intact SM [7,14]. At the same time at CG a number of inflammatory and degenerative processes in the gastric epithelium develops [19], which, possibly may cause the increased risk of erosive gastropathy at NSAID-therapy.…”
Section: Introductionmentioning
confidence: 99%